An Assessment of Algae and cyanotoxins in small-holder Aquaculture farms in Vhembe, South Africa - Tshifura, Rudzani Alice (My University, 2018)
In South Africa, inland aquaculture is on the increase, especially among the rural communities. Thus aquaculture is able to provide a source of employment and improve rural incomes. This study assessed algae species and their cyanotoxins in small holder production in Vhembe district, Limpopo, South Africa. Thirteen study sites were selected to assess the algae species and their cyanotoxins. The water samples were collected in four quarters and analysed for water temperature, pH, total dissolved solids, Electrical conductivity, phosphates, nitrates, chlorophyll, cyanobacteria, cyanotoxins, metal species and quality of the water in the fish ponds. In the 1st quarter of the year there was variation in Water Temperature (23.7oC-31.4oC), pH (5.5-9.6), EC (3.82-46.8μS/cm), TDS (2.4-45 mg/L), Phosphate (0.0-1.09mgL-1), Nitrates (0.0-1.00mgL-1), Chlorophyll-a (5.8-11.5mg/m-3). In the 2nd quarter there was variation inwater temperature (22.4-25.0oC), pH (6.6-8.8.9), EC (19.23-21.47μS/cm), TDS (12.5-17.9 mg/L), Phosphate (1.64-1.84mgL-1), Nitrates (1.02-1.88mgL-1), Chlorophyll-a (4.6-15.6mg/m-3). In the 3rd quarter there was variation for water temperature (22.9-25.0oC), pH (7.5-9.1), EC (7.91-293.3μS/cm), TDS (11.7-180.9 mg/L), Phosphate (1.10-1.80mgL-1), Nitrates (1.28-1.84mgL-1),Chlorophyll-a (6.8-15.6mg/m-3). In the 4th quarter there was variation forwater temperature (23.5-30.3), pH (7.1-9.3), EC (18.24-623μS/cm), TDS (23.7-136.4 mg/L), Phosphate (1.45-1.99mgL-1), Nitrates (1.43-1.68mgL-1), Chlorophyll-a (6.6-25.9mg/m-3). The metal content of the fish pond water was variable throughout the year but with moderate levels of Al, Cd, Cr, Mn, Fe, Cu, Zn and Ba were found. The metal Fe, exceeded the DWAF guideline values during this first quarter. The presence of Cd in the fish pond water could be attributed to rainfall eroding the earthen embankments of the fish pond. The results of physico-chemical parameters promotes the growth of cyanobacteria in the fish ponds. Flow cam and SEM were used to identify the cyanobacteria species and most cyanobacteria identified are hazard to human health, fish and other aquatic organisms. Molecular technologies were used to identify cyanotoxins and there was no cyanotoxins detected which was concluded that during collection of water samples no cyanobacteria produced toxins.
MESHWR
Department of Hydrology and Water Resources
Keywords: Cyanotoxins; Cyanobacteria; UCTD; Aquaculture; Rural communities; Tilapia fish fixing; 579.80968257; Algae -- South Africa -- Limpopo; Aquaculture -- South Africa -- Limpopo; Algae culture -- South Africa -- Limpopo; Agriculture -- South Africa -- Limpopo; Cyanobacterial toxins -- South Africa -- :Limpopo; Aquatic resource -- South Africa -- Limpopo; Crytogams -- South Africa -- Limpopo; Algology -- South Africa -- Limpopo; Freshwater algae -- South Africa -- Limpopo; Green algae -- South Africa -- Limpopo